Rare and de novo duplications containing SHOX in clubfoot. Issue 12 (9th June 2020) - Sadler, Brooke; Haller, Gabe; Antunes, Lilian; Nikolov, Momchil; Amarillo, Ina; Coe, Bradley; Dobbs, Matthew B.; Gurnett, Christina A.
Abstract : Introduction: Congenital clubfoot is a common birth defect that affects at least 0.1% of all births. Nearly 25% cases are familial and the remaining are sporadic in inheritance. Copy number variants (CNVs) involving transcriptional regulators of limb development, including PITX1 and TBX4, have previously been shown to cause familial clubfoot, but much of the heritability remains unexplained. Methods: Exome sequence data from 816 unrelated clubfoot cases and 2645 in-house controls were analysed using coverage data to identify rare CNVs. The precise size and location of duplications were then determined using high-density Affymetrix Cytoscan chromosomal microarray (CMA). Segregation in families and de novo status were determined using qantitative PCR. Results: Chromosome Xp22.33 duplications involving SHOX were identified in 1.1% of cases (9/816) compared with 0.07% of in-house controls (2/2645) (p=7.98×10 −5, OR=14.57) and 0.27% (38/13592) of Atherosclerosis Risk in Communities/the Wellcome Trust Case Control Consortium 2 controls (p=0.001, OR=3.97). CMA validation confirmed an overlapping 180.28 kb duplicated region that included SHOX exons as well as downstream non-coding regions. In four of six sporadic cases where DNA was available for unaffected parents, the duplication was de novo . The probability of four de novo mutations in SHOX by chance in a cohort of 450 sporadic clubfoot cases is 5.4×10 –10 . Conclusions: Microduplications of the pseudoautosomal chromosome Xp22.33 region (PAR1) containing SHOX and downstream enhancer elements occur in 1% of patients with clubfoot. SHOX and regulatory regions have previously been implicated in skeletal dysplasia as well as idiopathic short stature, but have not yet been reported in clubfoot. SHOX duplications likely contribute to clubfoot pathogenesis by altering early limb development.